Untangle those stethoscopes; never too early to start reflecting! Qualitative review of a reflective practice group for clinical undergraduate medical students. (13th April 2021) - Jordan, E.; Patel, S.; Mcguire, E.; Noonan, P.; Mccarthy, G.
Abstract : Introduction: Equipping our medical students with as many tools as possible to cope with the challenges that they will inevitably face has never been more important than it is today. Objectives: The aim of this study was to examine the effectiveness of a reflective practice (RP) group for medical students, particularly with adaptation to COVID-19 and transition to video. Methods: A pilot programme of RP for 3 rd  year medical students commencing their clinical placement was run by the Sligo Medical Academy, NUIG in Ireland between January – April 2020. This group for nine students was initially run face-to-face but pivoted to an online group in March 2020 with the COVID-19 pandemic. Data was collected through one-to-one interviews with all student participants and the facilitator (n=10). Interviews were recorded and transcribed. Data were analysed using thematic content analysis. Results: Our analysis identified four main discussion themes: transition to clinical environment, gender in the workplace, building professional identity and family and support systems. The students who continued the RP group over zoom during the COVID-19 pandemic particularly identified with the theme of support systems and solidarity. The smooth transition to zoom and its effectiveness in a time of social distancing were discussed. Identified challenges related primarily to timing of the RP group, particularly after a full day of placements or time differences for international students overseas. Conclusions: Reflective practice programmes are not routinely offered to medical students in Ireland currently and this study gives recommendations on implementing and improving experiences of undergraduate training based on RP. Disclosure: No significant relationships.